The Influence of Organizational Citizenship Behavior, Workload, and Compensation on Turnover Intention at CV. Maju Bersama Kisaran - Feriani Astuti Tarigan; Robin Robin; Philip Philip (SEAN Institute, 2026)
The purpose of this study was to determine the effect of organizational citizenship behavior, workload, and compensation on turnover intention at CV. Maju Bersama Kisaran. The research methodology used was a quantitative descriptive method. The type of data used in this study was quantitative data, namely data obtained in the form of numbers. The data sources consisted of primary data and secondary data. Primary data were obtained through questionnaires distributed to respondents, while secondary data were obtained from documents and literature related to the research problem. The population in this study consisted of all 79 employees working at CV. Maju Bersama Kisaran. Since the population only consisted of 79 employees, the sampling technique used was saturated sampling, where the entire population was used as the research sample. Based on the results of the study, it can be concluded that organizational citizenship behavior had a negative and significant effect on turnover intention, while workload had a positive and significant effect on employee turnover intention at CV. Maju Bersama Kisaran. In addition, compensation also affected turnover intention, and organizational citizenship behavior, workload, and compensation simultaneously affected employee turnover intention at CV. Maju Bersama Kisaran. The company is expected to use the results of this study as evaluation material to improve organizational citizenship behavior, manage workload proportionally, and improve the compensation system in order to reduce employee turnover intention.